Forestry activity in Portugal within the context of the European Union: a cluster in agricultural economics for sustainable development - Martinho, Vítor (2016)
Forestry activities may be important complements to a farmer’s income within the context of agricultural economics, or autonomous production, with determining factors upon rural dynamics and sustainable development. Taking these ideas into account, the objective of this study was to analyze the importance of forestry for sustainability in Portugal, namely in rural regions, comparatively with the context verified across other countries in the European Union. For this, data from the Eurostat (Several statistics. European Union Statistics, Luxembourg, 2015) for the European countries were used, over the period 1990–2014, and for variables that allowed to capture the interrelationships among forest indicators and economic, social and environmental variables. This statistical information was analyzed from a descriptive perspective and using the pairwise correlation matrix (complemented with the Granger causality Wald tests), through the Stata (Statistics/data analysis. StataCorp, LP, College Station, TX, 2015) software, to understand the relationships between the different indicators. As a main finding, it is worth referring that Portugal has had, in this period, a small impact on the European Union forestry conjuncture, but with great potential, namely in terms of agricultural and rural economic sustainability.